2016
DOI: 10.1007/s11739-016-1580-x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the management of atrial fibrillation in the emergency department: a critical appraisal

Abstract: Several guidelines often exist on the same topic, sometimes offering divergent recommendations. For the clinician, it can be difficult to understand the reasons for this divergence and how to select the right recommendations. The aim of this study is to compare different guidelines on the management of atrial fibrillation (AF), and provide practical and affordable advice on its management in the acute setting. A PubMed search was performed in May 2014 to identify the three most recent and cited published guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Despite this, and in absence of specifically-designed risk scores, stratification with CHA 2 DS 2 -VASc and HAS-BLED is still recommended by experts also in critical illness 6 . This is in line with other indications for the AF management in an emergency care setting observed in several guidelines 4 . However, since the in-hospital occurrence of thromboembolism or bleeding in a critically ill patient could radically modify the prognosis 7 , more accurate solutions are required to correctly stratify the risk of this specific category of subjects.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite this, and in absence of specifically-designed risk scores, stratification with CHA 2 DS 2 -VASc and HAS-BLED is still recommended by experts also in critical illness 6 . This is in line with other indications for the AF management in an emergency care setting observed in several guidelines 4 . However, since the in-hospital occurrence of thromboembolism or bleeding in a critically ill patient could radically modify the prognosis 7 , more accurate solutions are required to correctly stratify the risk of this specific category of subjects.…”
Section: Introductionsupporting
confidence: 89%
“…Nowadays, the baseline assessment of thromboembolic and bleeding in the routine management of clinically stable AF patients represents a pivotal step for all the major international guidelines 3 . Notwithstanding, the management of AF in the critically ill patient is still object of debate 4 , being both thromboembolic and hemorrhagic risk difficult to be assessed for several confounding factors, as coagulation abnormalities, platelet number and function alterations, drug therapies, drug-drug and drug-pathology interactions which can occur in those patients.…”
Section: Introductionmentioning
confidence: 99%
“…Even if lower than in HFrEF, the prevalence of hormone deficiency (HD) in HFpEF was remarkable, considering that more than half of HFpEF had at least 1 hormone deficiency. In this study a major prevalence of atrial fibrillation (AF) in HFpEF was recorded, as expected [51,52]. However, the small sample size did not allow any further investigation regarding the occurrence of AF in patients with hormonal deficiencies and HFpEF.…”
Section: Prevalence and Clinical Meaning Of Gh/igf-1 Impairment In Chfmentioning
confidence: 59%
“…A recent study performed by the residents of the European Federation of Internal Medicine (EFIM) Summer School, comparing three major guidelines on atrial fibrillation management in an acute setting, revealed that evidence on this particular clinical topic is largely based on expert opinion rather than clinical trials. While there is broad agreement on the management of the haemodynamically unstable patient and the use of drugs for rate-control strategy, there is less agreement on drug therapy for rhythm control but no agreement on several other clinical questions [45].…”
Section: Physicians' Behaviourmentioning
confidence: 99%